Mobilizing concerted action for AWD+ outscaling in Bangladesh - CGIAR Research Program on Climate Change, Agriculture and Food Security (2017)
In Bangladesh, Dr Akram Chowdhury, chairman of Barind Multipurpose Development Academy (BMDA) and parliament member, discussed with Dr. Ole Sander his intention for a joint proposal development to disseminate AWD+ to a group of BMDA deep tube-well areas in the sub-districts (Upazila) level. The proposal will be submitted to the Krishi Gobeshona Foundation (KGF) for funding.